L-Hollow modules - Thaer Z. Khlaif; Nada K. Abdullah (Tikrit Journal of Pure Science)
To consider R is a commutative ring with unity,  be a nonzero unitary left   R-module,  is known hollow module if each proper submodule of  is small.  L-hollow module is a strong form of hollow module, where an R-module  is known L-hollow module if  has a unique maximal submodule which contains each small submodules. The current study deals with this class of modules and give several fundamental properties  related with this concept.